HUBUNGAN ANTARA KEPUASAN KERJA, KOMITMEN ORGANISASIONAL, DAN KEINGINAN UNTUK KELUAR KARYAWAN PADA STIE CENDEKIA - Ari Kuntardina; Ahmad Saifurriza Effasa (Jurnal Manajemen dan Penelitian Akuntansi (JUMPA), 2014)
This study examined the relationship of job satisfaction, organizational commitment and intention to leave. We use correlational research methods andregression analysis. The technique of collecting data through questionnaires and using a Likert scale. The results showed job satisfaction only have a relationship with affective commitment. Affective commitment has relationship with intention to leave. The negative relationship of job satisfaction and affective commitment, it’s means that the higher the job satisfaction and affective commitment of employees, hence the smaller intention to leave organizations.